Influence of NleH effector expression, host genetics, and inflammation on Citrobacter rodentium colonization of mice - Feuerbacher, Leigh Ann; Hardwidge, Philip R. (My University, 2014)
The Escherichia coli NleH1 and NleH2 virulence proteins differentially regulate host transcription of innate immunity genes. The mouse pathogen Citrobacter rodentium encodes one NleH protein, which functions equivalently to E. coli NleH1. We examined the impact of host genetics and intestinal inflammation on the contribution of NleH to C. rodentium colonization of mice differing in LPS responsiveness. NleH expression was detrimental to C. rodentium in C57BL/10ScNJ mice, which do not mount LPS-induced inflammatory responses. This phenotype was reversed if inflammation was induced by chemical means. C. rodentium that expressed both E. coli NleH1 and NleH2 was hypervirulent in C3H/HeJ mice.
Keywords: Escherichia coli; Innate immunity; NF-kappa B (NF-κB); NleH1; Mouse